Korelasi Sertifikasi dan Motivasi Kerja terhadap Kinerja Guru di Masa Pandemi Covid-19 - Amruddin Amruddin; Wresni Pujiyati; Ipong Dekawati (Journal of Education and Teaching (JET), 2021)
This study aims to obtain a description of the correlation between teacher certification, teacher work motivation, and teacher performance at the Wanasari District Elementary School, Brebes District. This research uses a quantitative approach with descriptive analysis method. The population and sample of this study were certified elementary school teachers. The results showed that (1) there was a significant correlation between teacher certification and teacher performance. (2) there is a significant correlation between work motivation and teacher performance. (3) there is a significant correlation between teacher certification and work motivation simultaneously with teacher performance.